ANALISIS PENGARUH BRAND IMAGE DAN CORPORATE BRANDING TERHADAP BRAND EQUITY SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN OPERATOR SELULER TELKOMSEL DI KOTA SEMARANG - Purnomo, Singgih; Indriani, Farida (Diponegoro Journal of Management, 2018)
This research aims to find the infulence of brand image and corporate branding on brand equity and its impact on customer loyalty. Furthermore, it aims to find out the role of brand equity in mediating on customer loyalty.This research was conducted on Telkomsel operator customers in Semarang City have been using Telkomsel for minimum one year and had used other celluler operators. Sampling method  in  this  research  is  non-probability  sampling  with  purposive  sampling  technique.  The number   of   samples   collected   as   many   as   100  respondents   through  the   distribution  of questionnaires. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression tests, f-test, determination test, hypothesis test (t statistic test), and Sobel test.The  results  showed  that  the  variables  of  brand  image  and  corporate  branding  in  a significantly and positively impact on brand equity. Variable corporate branding has a significant and positive impact on customer loyalty. But the brand image variable has no effect on customer loyalty. Meanwhile brand equity as an intervening variable has a positive and significant impact on customer loyalty.